A meta-analytic test of the imagined contact hypothesis. (January 2014) - Miles, Eleanor; Crisp, Richard J.
Imagined intergroup contact (Crisp & Turner, 2009) is a new indirect contact strategy for promoting tolerance and more positive intergroup relations. Despite its relatively recent inception, there have now been over 70 studies showing that imagining a positive interaction with an outgroup member can reduce prejudice and encourage positive intergroup behavior. With this meta-analysis, we provide the first quantitative review of imagined contact effects on four key measures of intergroup bias: attitudes, emotions, intentions, and behavior. We also test for moderators arising from both group and study design characteristics. The analysis found that imagined contact resulted in significantly reduced intergroup bias across all four dependent variables (overall d+ = 0.35). The effect was significant for both published and unpublished studies, and emerged across a broad range of target outgroups and contexts. The effect was equally strong for explicit and implicit attitude measures, but was stronger on behavioral intentions than on attitudes, supporting the direct link between imagery and action proposedly underlying mental simulation effects. Most design characteristics had no significant impact, including valence of the imagined interaction, type of control condition, and time spent imagining contact. However, the more participants were instructed to elaborate on the context within which the imagined interaction took place, the stronger the effect. The imagined contact effect was also stronger for children than for adults, supporting the proposition that imagined contact is a potentially key component of educational strategies aiming to promote positive social change.